Analisis Pemanfaatan e-Goverment sebagai Media Pelayanan Publik di Indonesia - Dedi Ramadhan; Agil Furgaan; Ifan Setiawan; Ali Ibrahim (P3M Politeknik Negeri Banjarmasin, 2019)
The development of E-Government in Indonesia shows a decrease and increase every year. The indices that influence include the Online Service Index, the Telecommunication Infrastructure Index, the Human Capital Index. This paper aims to analyze the application of E-Government in Indonesia. This research uses data from a UN survey through the UN E-Government Knowledgebase. Based on the results of this study, the index of E-Government implementation in Indonesia has decreased and increased 0.4949 in 2012, 0.4487 in 2014, 0.4478 in 2016 and 0.5258 in 2018, which shows that the implementation of E-Government in Indonesia has decreased in the period 2012-2016 and an increase in the 2016-2018 period, which means that the Indonesian government began to improve E-Government in Indonesia.